Cancer incidence and mortality trends from 2003 to 2014 in Italy. Issue 2 (April 2019) - Buzzoni, Carlotta; Crocetti, Emanuele; Guzzinati, Stefano; Dal Maso, Luigino; Francisci, Silvia
Objective: To evaluate short-term (2003–2014) cancer incidence and mortality trends in Italy. Methods: Italian Cancer Registries data, available in the AIRTUM database, from 17 out of 20 regions were used. The number of incident cases and deaths were estimated for those registries and those years with incomplete information. Age-standardized rates, overall and stratified by geographic area, region, sex, cancer site, and major age group, were computed. Time trends were expressed as annual percent change of rates. Results: In Italy, among males, incidence rates for all cancers showed during 2003–2014, a significant decrease (−0.9%/year), with stronger reductions in the northwest (−1.3%/year) and northeast (−2.0%/year since 2006) than in central (−0.7%/year) and southern (−0.4%/year) areas. Among females, a weak but significant overall reduction was detected (−0.1%/year), with a stronger decrease in the northwest (−0.5%/year). Incidence increased among women in the south (0.3%/year) of Italy. Mortality decreased in both sexes (−1.0%/year among males and −0.5%/year among females), but not in the south, where rates had a stable tendency. Conclusions: Incidence among males decreased, supported by trends for prostate, lung, colorectal, and urinary bladder cancers; among females the. The overall cancer incidence trend was stable, or even decreasing, in the northern and central areas and increasing in the southern areas, due to lung, thyroid, and melanoma rising trends. Study results provided information on the outcomes, in terms of cancer incidence and mortality, of primary and secondary prevention measures employed by regional health systems.